Analisis Yuridis Pembatalan Pengangkatan Anak oleh Orang Tua Angkat: Studi Putusan Pengadilan Negeri Nganjuk - Said Rizal; Risky Lubis (Jurnal Hukum Lex Generalis, 2025)
Child adoption is a crucial aspect of Indonesia’s family law, offering a solution for couples unable to have children while ensuring protection and welfare for adopted children. Although regulated by various laws, adoption practices still face challenges—particularly in cases of annulment due to conflicts between adoptive parents and adopted children. However, no specific regulation governs the annulment process, creating legal uncertainty. This study uses a normative juridical method to analyze the legal aspects of adoption annulment in Indonesia, referencing cases such as Decision No. 31/Pdt.G/2022/PN.Njk. The findings show that judges base decisions on the best interests of the child. In this case, the annulment occurred when the child chose to return to biological parents, ending the civil relationship with the adoptive parents and restoring parental rights. The case highlights the urgent need for clearer regulations on adoption annulment.